The effect of applying total quality standards on job performance – An applied study for workers in the Saudi Red Crescent \ Saudi Arabia – - Alshehri, Mohammad Hassan; Al-Shahrani, Saeed Ayed Nasser (Journal of Economic, Administrative and Legal Sciences, 2020)
On the performance of staff in the Saudi Red Crescent. The researcher used the analytical descriptive method, using the questionnaire performance to measure the opinions of the respondentsusing the statistical analysis program (SPSS) to analyze the data collected. The results of the study confirm the existence of an effect in applying the comprehensive quality standards on the job performance in the Saudi Red Crescent Authority at a high level on all criteria, and the study also found that the level of application of the comprehensive quality standards with all its criteria (continuous improvement, zero errors, focus on the beneficiaries) where It represents between 3.39 and 3.57 out of 5, and the level of job performance in the Saudi Red Crescent Authority is relatively high, as it represents 3.33 out of 5.The study recommends the need to pay attention to the application of TQM standards and to focus on the most important standards and impact on job performance.
Keywords: total quality management; job performance